Guiding and collimating the fast electrons by using a low-density-core target with buried high density layers. (13th December 2016) - Lv, Chong; Wan, Feng; Hou, Ya-Juan; Jia, Mo-Ran; Sang, Hai-Bo; Xie, Bai-Song; Liu, Shi-Bing
Abstract: A low-density-core target with buried high density layers is proposed to improve the transport of fast electrons and involved problems are investigated by using two-dimensional particle-in-cell simulations. It is demonstrated that this target can collimate the fast electrons efficiently and lead to a better beam quality. The enhancement is attributed to the weakening of the two stream instability and the better collimation by the self-generated multilayer megagauss magnetic field as well as the baroclinic magnetic field. Comparing this to that without buried high density layers, the energy flux of fast electrons is increased by a factor of about 1.8 and has a narrower transverse distribution in space. Besides, the dependence of the efficiency on the target parameters is examined, and the optimal target parameters are also obtained. Such a target can be useful to many applications, such as fast ignition in inertial fusion.